Evaluación de riesgos laborales mediante la guía técnica Colombia (GTC 45) en el proceso de ensamblaje del automóvil M4 en la Empresa Ciauto Cia Ltda. - Jiménez Pujos, Cristian David (2018)
The identification and evaluation of risk factors for each of the tasks performed in the workplace, is the most important part of occupational safety and health as it preserves the integrity of the workers of the company CIAUTO CIA LTDA. The interpretation of the level of risk that determined the state in which the company developed was made through the use of a legal matrix in Ecuador such as GTC 45, with international methodologies, which allowed to assess the risks according to: the activities of work and identification of hazards, this evaluation was carried out to each of the 294 tasks in the 34 jobs that correspond to the process of assembly of the M4 car. The needs of the company regarding the assembly process were visualized and intervention measures such as: substitution, elimination, energy controls, administrative controls, EPP'S were recomnended. The project generates great importance in the social part since knowing the risks allows the workers to create a preventive culture to take care of their health, in the economic part it will allow the company to avoid expenses for occupational diseases and accidents that the workers may suffer if the intervention measures are not taken into account.